Association of Porcine Heparanase and Hyaluronidase 1 and 2 with Reproductive and Production Traits in a Landrace–Duroc–Yorkshire Population - Rempel, Lea A.; Freking, Brad A.; Miles, Jeremy R.; Nonneman, Dan J.; Rohrer, Gary A.; Vallet, Jeffrey L.; Schneider, James F. (Frontiers in Genetics, 2011)
The ovary and placenta are dynamic structures requiring constant modification both structurally and through cell-cell communication capabilities. The extracellular matrix and basement membranes are primarily composed of a milieu of glycosaminoglycans, including heparan sulfate and hyaluronan. Heparanase (HPSE) and hyaluronidases (HYAL) are responsible for degrading heparan sulfate and hyaluronan, respectively. Therefore, the objective of this study was to evaluate the relationship of SNPs distinct to HPSE, HYAL1, and HYAL2 with measurements of reproduction and production traits in swine. Single trait associations were performed on a Landrace-Duroc-Yorkshire population using SNPs discovered and identified in HPSE, HYAL1, and HYAL2. Analyses were conducted on an extended pedigree and SNPs were found to be associated with reproductive and production traits. Prior to multiple-testing corrections, SNPs within HPSE were weakly associated (P < 0.03) having additive effects with age at puberty (-2.5d + 1.08), ovulation rate (0.5 corpora lutea + 0.24), and number of piglets born alive (0.9 piglets + 0.44). A HYAL1 and two HYAL2 SNP were nominally associated (P < 0.0063) with number of piglets born alive after multiple-testing corrections (effects between 1.02 and 1.44 piglets), while one of the same HYAL2 markers maintained a modest association (P = 0.0043) having a dominant effect with number of piglets weaned (1.2 piglets + 0.41) after multiple-testing correction. Functionally, HPSE and HYAL1 and 2 have been shown to participate in events related to ovarian and placental activity. SNPs from these studies could potentially assist with understanding genetic components underlying sow lifetime productivity as measured by piglet survivability based on number born alive and number weaned, thereby contributing to a greater number of pigs/sow/year.